Juridical Analysis Of Controlling Abandoned Land Of The National Land Agency In The Context Of Realizing Community Welfare (Research Study At The Land Agency Of Riau Islands Province) - Deko Andesta; Erni Yanti; Ramon Nofrial; Soerya Respationo (Badan Penerbit STIEPARI Press, 2023)
In order to maintain land quality and improve community welfare, rights holders, management rights holders, and basic holders of land control are expected to protect and maintain their land and not neglect it. The problem of this research is legal regulation, controlling abandoned land, and the legal consequences of controlling abandoned land by the National Land Agency in order to realize community welfare. The results of the research on abandoned land are land rights, land with management rights, and land obtained based on control over land, deliberately not cultivated, not used, not exploited, and/or not maintained which is regulated based on Government Regulation Number 20 of 2021 concerning Controlling Areas and Abandoned Land Controlling Areas and Abandoned Land. Controlling abandoned land by the National Land Agency in order to realize community welfare includes inventory of land indicated to be abandoned, supervision of inventory of land indicated to be abandoned, reporting of the results of the inventory of land indicated to be abandoned, as well as follow-up to the results of the inventory of land indicated to be abandoned; The legal consequence of controlling abandoned land by the National Land Agency in the context of realizing community welfare is for the owner of the rights to abandoned land, namely that the land rights will be canceled and result in the end of the land rights. Efforts to overcome control or ownership of abandoned land are closely related to existing land policies. The application of norms in their implementation is identical to the implementation of rights and obligations. The government should perfect or improve the regulations for controlling and utilizing abandoned land, especially regarding the concept/understanding of abandoned land and the criteria to be further clarified and simplify the mechanism for implementing control, starting with identification work by the task force; provide recommendations for identification results to the Regency/City assessment team, Regional Offices and even to the Minister who will make a determination that a plot of land is abandoned. This is recommended so that there are no differences in perception between officers in the field.